A Educação Sexual na formação do/a pedagogo/a no estado do Paraná - Lorenzi, Franciele (2017)
The purpose of the study is the curricular matrices and the undergraduate courses in Pedagogy regarding to Sexual Education. The main objective was to identify subjects that contemplate Sexuality and Sexual Education as a curricular component in their matrices and/or in the syllabuses of the subjects, in the mentioned course of the public universities in Paraná State. We seek to investigate on which paradigms Sexual Education is based and what was the contingent of inferences and economic, ethical, political, religious, technological and social determinants that led to the institutionalization of the theme by social institutions. We carried out a theoretical-bibliographic revision and the scientific productions in the post-graduations stricto senso about the subject Sexual Education, Curriculum and Pedagogical Courses, in the databases BDTD, SCIELO, Public Domain, CAPES and in the digital libraries of the public universities in Paraná State. We detected fourteen (14) master's dissertations and one (01) doctoral thesis, however, we did not identify research that discussed our object of study. We took as basis the marxist theory, and as a theoretical-methodological reference, the historical-dialectical materialism, in order to identify and analyze the contradictions, possibilities and limitations in the Pedagogy Courses, with respect to the formation of the pedagogues in Education Sexual. It is a qualitative and quantitative research that makes a documentary analysis of the curricular matrices and current ementaries of the course. We trace the historical course of public policies to education in Brazil in order to understand how the National Curricular Guidelines for the Pedagogy Course (DCNCP, 2006) materialized, which started to have teaching as a basis for its identity. In this way, we investigate if the pedagogue has been receiving historical training and the necessary theoretical background, to work the Human Sexuality in the exercise of teaching. We identified thirty-one (31) undergraduate courses in Pedagogy, of which we located the offer of two (02) subjects, in the optional modality, related to Sexual Education. These courses cover four (04) of the 31 courses and are offered at one of the state universities and at the federal university. In this sense, we observed the discrepancy and fragmentation between the documents that sustain the Basic Education and the Higher Education in front of the public policies. At the present time, we faced an economic, political, moral and social crisis which reflects a theoretical and educational crisis. To do so, adapting the PPPs and / or PPCs of the Pedagogy courses to the bureaucratic and legal requirements do not account for meeting the challenges and demands that emerge from the social context and enter the universities and schools. It is necessary to bring about a process of restructuring the Curriculum as a whole, which means deconstructing or overcoming the fragmentation of the pedagogue's practice, since who defines this practice is not always the same subject that practices it. We defend Emancipatory Sexual Education, in the initial formation and in the continuous formation of teachers, that aims to overcome the fragmentation of Sexuality and that allows us the political, historical, philosophical and anthropological exercise of authentic form.